AFFAIR AS PORTRAYED IN F. SCOTT FITZGERALD THE GREAT GASTBY - Mato, Juwita Lanti; Mamentu, Agustine C.; Damopolii, Veronika L. F. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of this research is to describe the affair as portrayed in the novel The Great Gatsby by F. Scott Fitzgerald. Affair that occurs and is carried out deliberately to fulfill the characters' dissatisfaction, wealth and selfishness. This results in a negative impact and becomes an inappropriate example for society. In analyzing the data psychological theory will be used. Data was collected from the main source of the novel itself and secondary sources in the form of several books, journals, web pages and other references used to support this research. Analysis of concept use is based on text interpretation and novel context. The results of this research describe an affair carried out deliberately by the character of the novel